PIDANA MATI BAGI TINDAK PIDANA KORUPSI DI INDONESIA - Hisyam Fahmi (2021)
ABSTRACT Corruption has been widespread, it is increasingly systematic, causing losses to the national economy. In the article 2 paragraph (2) of Law Number 31 of 1999 concerning the Eradication of Criminal Acts of Corruption states that the death penalty can be imposed under certain conditions, however until today there is no corruptor has been sentenced to the death penalty. This study discussed issues related with corruption, including:first, how is the urgency of death penalty applied to corruptors in Indonesia, and secondly how is the implementation of death penalty for corruptors in Indonesia. The method applied in this study was a normative legal research type, with statutory approach and a conceptual approach. This study used primary legal materials, and data was collected by literature study, then analyzed using qualitative methods. The following conclusions can be drawn from this study: first, until now there has been no implementation of the death penalty to punish perpetrators of corruption in Indonesia, because the indicators of the formulation are still multi-interpreted and limited to the provisions of Article 2 paragraphs (1) UUTPK. Second, corruption is classified as a serious crime, so the death penalty is still needed and relevant to be applied in Indonesia as a deterrent effect. Keywords: Penalty, Death Penalty, Corruption